2020
DOI: 10.3892/br.2020.1328
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis shows that TOP2A functions as a key candidate gene in the progression of cervical cancer

Abstract: Cervical cancer (CC) is one of the most prevalent types of cancer affecting females worldwide. However, the molecular mechanisms underlying the development and progression of CC remains to be elucidated. Taking the high incidence and mortality rates amongst women into consideration, the identification of novel biomarkers to prevent CC is of great significance and required to improve diagnosis. Using three raw microarray datasets from the Gene Expression Omnibus database, 188 differentially expressed genes (DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 73 publications
2
20
0
Order By: Relevance
“…FBXO5 has been suggested to play crucial roles in the development of HCC, cervical cancer and squamous-cell lung carcinoma in the latest research on bioinformatics analysis [46][47][48]. Also, we got the similar results in BC.…”
Section: Discussionsupporting
confidence: 62%
“…FBXO5 has been suggested to play crucial roles in the development of HCC, cervical cancer and squamous-cell lung carcinoma in the latest research on bioinformatics analysis [46][47][48]. Also, we got the similar results in BC.…”
Section: Discussionsupporting
confidence: 62%
“…There were 83 upregulated genes and 7 downregulated genes in the CIN-CC group. Furthermore, 155 upregulated genes in the N-CC group, including TCAM1P , MCM2 , HS6ST2 , AIM2 , CDKN2A , RFC4 , PLOD2 , APOC1 and CENPF [ 19 ], were shared among the three datasets. Among the 208 downregulated genes, 51 were shared among the three datasets: TMPRSS11B , BBOX1 , ZSCAN18 , ENDOU , KLK8 , ANKRD35 , A2ML1 , CRYAB , MAL , VSIG10L , ECM1 , SPINK5 , TM7SF2 , SPINK7 , PRSS27 , RBP7 , PRSS3 , ACPP , HPGD , CWH43 , RHCG , SCEL , TP53I3 , SPRR2C , CRABP2 , HCG22 , DMKN , PRSS2 , CLIC3 , SPNS2 , LCE3D , FUT3 , RDH12 , CRNN , CEACAM7 , LYNX1 , MYZAP , KRTDAP , NDRG4 , SLC5A1 , GPX3 , PPP1R3C , SLURP1 , SLC24A3 , THSD4 , PSCA , CDA , FAM3D , CFD , HOPX , and CRCT1 .…”
Section: Resultsmentioning
confidence: 99%
“…Critical subnetworks might strongly contribute to the occurrence and development of cervical cancer and have high diagnostic value. Further analysis showed that NUSAP1 [ 36 ] , TOP2A, KIF2C [ 37 ] , NDC80 [ 23 ] , ASPM [ 21 , 38 ] , KIF20A [ 39 ] , CDK1 [ 19 , 38 ] , KIF11 [ 40 , 41 ] , BIRC5 [ 42 ] , MCM2 and CHEK1 [ 40 , 41 , 43 ] were high scoring hub genes and showed significantly upregulated expression in cervical cancer tissues compared with normal tissues ( P < 0.01). By analyzing the prognostic values of the hub genes from the 12 subnetworks, a total of 14 potential molecular targets ( MCM2 [ 23 , 35 , 44 46 ], TOP2A [ 19 , 35 , 40 ], BLM, RMI2 , EXO1 , RFC4 , PSCA , KNTC1 , CDC45 , GINS2 , CXCL8 , TNFAIP6 , CXCL5 , and CDA ) were obtained and annotated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described an abnormal regulation of the cell cycle mechanism that plays a vital role in both tumorigenesis and progression, including that detected in CC [ 26 ]. In this study, a more complex alteration mechanism at both mRNA and miRNA is observed.…”
Section: Discussionmentioning
confidence: 99%